Students' Perceptions of Online Learning on Social Interaction/Persepsi Mahasiswa pada Pembelajaran Online terhadap Interaksi - Salamah, Umi; Bashith, Abdul; Nurdiana, Ilfi; Said, Achmad (STAI Ma'had Aly Al-Hikam Malang, 2020)
This article aims to describe students' perceptions of online learning on social interaction. The method used is descriptive qualitative with observation instruments, online surveys, group discussion forums with the research subjects of the 2018 class of PGMI students STAI Ma'had Aly Al-Hikam Malang, Indonesia. The results of the study show that online learning on campus online learning is integrated with SIAKAD and other applications such as google classroom, WhatsApp, Zoom, Jitsi, google meet, etc. for teleconferencing during student presentations and discussions. Students are able to take online lectures well. The student's perspective on online lectures runs quite well despite some obstacles including internet connection, some materials are difficult to understand because they are only given assignments and discussions are carried out through siakad. The impact of online learning on social interactions, among others, is that communication and learning can run well and be flexible, there is miscommunication, and some have difficulty understanding the material.